Stylistic devices describing faith in the novel " Life of Pi" by Yann Martel and its Vietnamese equivalent translated by Trinh Lu - Hồ, Thị Thu Trang. (The University of Da Nang, 2015)
Introduction; Literature review and theoretical background; Research design and Methodology; ...